Designing Journeys Application Interface to Improve Indonesian UMKM Accessibility with a User Centered Design Approach - Putra, Anak Agung Adi Wiryya; Putra, I Gede Elang Perdana Dwi; Sudharma, Made Wahyu; Putra, I Made Dharma (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines the application of UI/UX principles to the "Journeys" mobile application to improve accessibility for MSMEs in the tourism sector, using the User-Centered Design (UCD) approach. Digital transformation in today’s era offers great opportunities for MSMEs to promote their products and services to a wider audience. The UCD methodology, supported by the User-Based Collaborative Filtering system, is the core of designing an application that is aligned with user needs. The research phase involved user surveys and Focus Group Discussions (FGD) to explore needs, which were then manifested in user personas and customer journey mapping. The UI/UX design was prototyped with Figma, resulting in intuitive interfaces for the welcome screen, login, user profile, as well as destination exploration, social interaction, and itinerary planning features. The "My Ratings" and "Forge Your Route" features demonstrate a commitment to usability principles and community-based content integration. The "Journeys" application is expected to encourage the digital growth of tourism MSMEs and expand their market reach, support the development of local tourism human resources and the effectiveness of digital promotion. Evaluation using the System Usability Scale (SUS) showed an average score of 90,75 placing the application in the "Excellent" category and confirming its ease of use.